2006
DOI: 10.1529/biophysj.105.069096
|View full text |Cite
|
Sign up to set email alerts
|

Chemical and Structural Disorder in Eumelanins: A Possible Explanation for Broadband Absorbance

Abstract: We report the results of an experimental and theoretical study of the electronic and structural properties of a key eumelanin precursor-5,6,-dihydroxyindole-2-carboxylic acid (DHICA)-and its dimeric forms. We have used optical spectroscopy to follow the oxidative polymerization of DHICA to eumelanin and observe red shifting and broadening of the absorption spectrum as the reaction proceeds. First principles density functional theory calculations indicate that DHICA oligomers (possible reaction products of oxid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

17
252
0
4

Year Published

2010
2010
2018
2018

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 255 publications
(273 citation statements)
references
References 52 publications
17
252
0
4
Order By: Relevance
“…The chemical disorder model posits that eumelanin is made of many chemically distinct species such that its broadband absorption spectrum results from the convolution over the spectra of these species. [29] However, it has been reported that the spectrum is affected by interactions among eumelanin protomolecules. [30] Recently, Buehler and co-workers, considering excitonic couplings between eumelanin oligomers (tetramers, pentamers, and octamers), found that the computational spectra with geometric (packing) disorder of a single species of DHI oligomers ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The chemical disorder model posits that eumelanin is made of many chemically distinct species such that its broadband absorption spectrum results from the convolution over the spectra of these species. [29] However, it has been reported that the spectrum is affected by interactions among eumelanin protomolecules. [30] Recently, Buehler and co-workers, considering excitonic couplings between eumelanin oligomers (tetramers, pentamers, and octamers), found that the computational spectra with geometric (packing) disorder of a single species of DHI oligomers ( Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Besides its pigmentation, eumelanin is also an efficient photoprotective pigment. The broadband absorption spectrum of eumelanin [1][2][3][4] is a result of biological evolution for protecting living organisms from intense sunlight 5,6 . Any gaps in the spectrum would leave living organisms vulnerable to these specific wavelengths of sunlight.…”
mentioning
confidence: 99%
“…The chemical disorder model is a widely accepted model to explain the broadband absorption spectrum of eumelanin 3,11,12 . Accordingly, eumelanin consists of many chemically distinct species and its broadband absorption spectrum is a result of averaging over the spectra of these species.…”
mentioning
confidence: 99%
“…The literature values for the absorption cross sections of DHI and DHICA vary depending on the solvent or pH; [49][50][51][52][53][54] , respectively. These results suggest that the absorption of the melanosome will vary with the relative content of DHI and DHICA.…”
mentioning
confidence: 99%